PRESUPPOSITION IN JOE BIDEN’S INAUGURATION SPEECH - Rahmadianto, Sadam; Herawati, Yayuk Widyastuti (Annual International Conferences on Language, Literature, and Media, 2021)
This study aims to find the types of presupposition used by Joe Biden in his inauguration speech. The meanings of the utterances are based on the context of the speech used theory of context proposed by Huang (2014). This study used a qualitative descriptive method because the researcher describes presupposition and meaning in speech. The data is taken from BBC News. The results of this study found 32 utterances that indicated presupposition. These utterances were classified into nine types of presupposition were used by Joe Biden in his inauguration speech. They are thirteen utterances of definite description, three utterances of factive predicates, two utterances of aspectual of state predicates, three utterances of iteratives, one utterance of implicative predicates, three utterances of quantifiers, one utterance of temporal clause, three utterances of cleft sentences, and three utterances of counterfactual conditional presupposition. The study did the analysis based on two types of context they are linguistic context and non-linguistic context. Besides, the study found that the utterances of Joe Biden in his inauguration speech have implied meanings that were not conveyed directly.